BECOMING AN OFFICER: SOCIOLOGICAL PORTRAITS OF CADETS IN PORTUGUESE MILITARY ACADEMIES - Bessa, F.; Carreiras, Helena; Ávila, P.; Xavier, Ana Isabel (RC01/ISA Conference “Transformations of the Military Profession, 2016)
This presentation focuses on the sociological portrait of cadets of Portuguese Military Academies, including the three branches of the Armed Forces (Army, Navy and Air-Force) and the National Gendarmerie. It draws on first results of an online survey conducted to all cadets in 2016 in the framework of a research project led by CISDI and based on a civilian-military partnership. It addresses the issues of institutional and professional orientations and the understanding of the officer’s role in a context of significant challenges to the military profession and the role of the Armed Forces in Portugal.